A Concise Formalization of Hyperrealism-Antirealism in Physics Using Neutrosophic Logic - Florentin Smarandache; Takaaki Fujita; Victor Christianto (Neutrosophic Sets and Systems)
In [6], the relationship between hyperrealism and antirealism in physics is proposed. HyperrealismAntirealism describes a spectrum where theories transition from being empirically grounded (realist) to speculative frameworks dominated by untestable assumptions, thereby detaching from observable reality. This paper presents a concise mathematical formalization of the spectrum of hyperrealism-antirealism in theoretical physics and the philosophy of science. We propose a method to quantify the extent to which a theory is “hyperreal” or “antirealist” using a ratio of testable to untestable statements. Additionally, we provide several theorems that outline the conditions under which theories shift into hyperreal or antirealist domains. Finally, we explore how Neutrosophic Logic [38] can capture intermediate degrees between realism and antirealism, offering a nuanced perspective on the spectrum.